Co-creating a suite of patient decision aids for parents of an infant or young child with differences of sex development: A methods roadmap - Lightfoot, Sophie; Carley, Meg; Brinkman, William; Gardner, Melissa D.; Gruppen, Larry D.; Liang, Noi; Pinkelman, Kendra; Speiser, Phyllis W.; Suorsa-Johnson, Kristina I.; VanderBrink, Brian; Wisniewski, Jessica; Sandberg, David E.; et al. (Frontiers in Urology, 2023)
Introduction: Parents and guardians of infants and young children with differences of sex development (DSD) often face numerous health and social decisions about their child’s condition. While proxy health decisions can be stressful in any circumstance, they are further exacerbated in this clinical context by significant variations in clinical presentation, parental lack of knowledge about DSD, irreversibility of some options (e.g., gonadectomy), a paucity of research available about long-term outcomes, and anticipated decisional regret. This study aimed to engage clinicians, parents, and an adult living with DSD to collaboratively co-design a suite of patient decision aids (PDAs) to respond to the decisional needs of parents and guardians of infants and young children diagnosed with DSD. Methods: We used a systematic co-design process guided by the Ottawa Decision Support Framework and the International Patient Decision Aids Standards (IPDAS). The five steps were: literature selection, establish the team, decisional needs assessment, create the PDAs, and alpha testing. Results: Our team of health professionals, parents, adult living with DSD and PDA experts, co-designed four PDAs to support parents/guardians of infants or young children diagnosed with DSD. These PDAs addressed four priority decisions identified through our decisional needs assessment: genetic testing, gender of rearing, genital surgery and gonadal surgery. All four PDAs include information for parents about DSD, the options, reasons to choose or avoid each option, and opportunities for parents/guardians to rate the importance of features of each option to clarify their values for these features. Qualitative feedback was positive from our team and when alpha tested with an interprofessional DSD speciality team in a single center . Conclusions: These PDAs are clinical tools designed to support parents/guardians to be involved in making informed DSD decisions; next steps are to determine parents’ decisional outcomes. While these tools are specific to DSD, the process through which they were co-designed is transferable to co-design of PDAs in other pediatric populations.